Implementing The Field Trip Method With Youtube Media To Improve Description Text Writing Skills - Nurhotimah, Siti; Suryadi, Suryadi (FKIP - Universitas Riau, 2023)
Writing is one way to express ideas and ideas about what has been seen, heard or experienced. To be able to produce or express flanguage through writing is an ability that necessitates encoding processes, and writing is an active and productive linguistic activity.This research was carried out because of the low desire to write and the lack of knowledge about writing descriptive texts. The benefits that can be obtained from the use of media through YouTube, among others, the teacher will find it easier to convey learning materials in a more interesting way, avoid the lecture method in delivering material, can facilitate various types of children's learning methods, students will be more enthusiastic about participating in learning with In presenting videos, the teacher will more easily invite students to be involved in learning activities. the purpose of this study is to determine the effect of using youtube media with the field trip method. The methodology of this investigation is experimental. This study employs a pre-experimental design known as the One-Group Pretest-Posttest Plan. The outcomes demonstrate an elevated dependence on Youtube media when composing descriptive texts using the field trip approach.